Analytical study of Pap smear reports over a period of 1 year in a tertiary care centre - Reyaz, Mehak; Nandi, Nupur; Aggarwal, Ritika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Cervical cancer is the fourth most common cancer in women. In India and other developing countries cervical cancer is the leading cause of morbidity and mortality. Cancer cervix continues to be most common genital carcinoma in India accounting for 80% of all female genital malignancies. Pre-invase lesions can spontaneously regress to normal or remain stable for long period or progress to a higher degree of dysplasia. Cancer of cervix is preventable if diagnosed at the pre-invasive stage with regular intervals of cytological screening by Papanicolaou (Pap) smears. The aim of the study is to analyse the pap reports in terms of normal findings, infections, premalignant lesions and invasive cancers. Methods: All women attending the outpatient department gynaecology at TMMC and RC Moradabad, Uttar Pradesh over a period of 1 year from august 2017-18 presented of obstetrics and with white discharge per vagina were screened for cervical cancer using pap smear. All the smears were reported as per the 2014 Bethesda system. Results: Out of 1392 Pap smear reports ASCUS was reported in 27 cases (2%), LSIL in 27 cases (2%), HSIL in 15 cases (1%), malignant cells in 15 cases (1%) and normal including the infection is reported in 1308 cases (94%). Conclusions: Early cervical epithelial changes can be identified by a Pap smear test, which is the primary screening test for detection of precancerous cervical intraepithelial neoplasia and the early stage of invasive cervical cancer.